ЭКОНОМИКАЛЫҚ ҚЫЗМЕТ САЛАСЫНДАҒЫ ҚЫЛМЫСТАР СУБЬЕКТІЛЕРІНІҢ КЕЙБІР ЕРЕКШЕЛІКТЕРІ (Journal of actual problems of jurisprudence, 2019)
From the subjective party all crimes in economic activities sphere are characterised by deliberate fault. An objazatelnym sign субьективной theparties of some structures are motive and the purpose.